Utilization of Online Learning for Islamic Religious Education Subjects During the Covid-19 Pandemic at SMP N Kelumbayan Barat Tanggamus - Dwi Febriana; Elisa Rumzanah; Fidian Abron (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
The use of online learning media for Islamic Religious Education (PAI) subjects at SMP N 1 Kelumbayan Barat is the focus of this study. The aim of this research is to explore the implementation of E-learning or online learning for PAI during the pandemic and assess the effectiveness of online learning media on student performance at SMP N 1 Kelumbayan Barat. The background of this study is related to the shift to online learning during the pandemic and the role of advanced technology, particularly the internet, in creating a learning medium known as e-learning or online learning. E-learning is applied in PAI instruction to facilitate the learning process for both teachers and students at SMP N 1 Kelumbayan Barat. The main issue addressed in this study is to examine the online applications used in the learning process, the teaching materials delivered by PAI teachers, and the online teaching methods utilized by instructors during the Covid-19 pandemic. This research is a field study, and data collection involves observations, interviews, and documentation. The data is systematically reduced, presented in a detailed descriptive form, and concluded at the end of the study.